38,000 flock “Jom Masuk U” carnival in Kuantan - UMP, PNC
Over 38,000 visitors flocked to the National Institutions of Higher Learning’s “Jom Masuk U” two-day carnival at the newly opened Sultan Ahmad Shah International Convention Centre (SASICC) in Kuantan on March 5-6, 2011.